Deformation of Polycrystalline MgO Up to 8.3 GPa and 1270 K: Microstructures, Dominant Slip-Systems, and Transition to Grain Boundary Sliding - Ledoux, Estelle Elisa; Lin, Feng; Miyagi , Lowell; Addad , Ahmed; Fadel, Alexandre; Jacob , Damien; Béclin , Franck; Merkel, Sébastien (Frontiers in Earth Science, 2022)
Ferropericlase is the second most abundant mineral in the Earth's lower mantle and and its mechanical properties have a strong influence on the rheology of this region. Here, we deform polycrystalline MgO, the magnesium end-member of ferropericlase, at conditions ranging from 1.6 to 8.3 GPa and 875 to 1270 K. We analyse the flow laws and microstructures of the recovered samples using electron microscopy and compare our observations with predictions from the literature. We identify a first mechanism for samples deformed at 1270 K, attributed to a regime controlled by grain boundary sliding accommodated by diffusion and characterized by a small grain size, no microstructural evolution, an absence of texture, and no intracrystalline deformation. At 1070 K and below, the deformation regime is controlled by dislocation-based plasticity. The samples show a more homogeneous grain size distribution, significant texture, and intracrystalline strains. In this regime, deformation is controlled by the <110>{110} slip system and a combined <110>{110} and <110>{100} slip, depending on pressure and temperature. Based on these results, we propose an updated deformation map for polycrystalline MgO at mantle conditions. The implications for ferropericlase in the Earth's lower mantle are discussed.